The persistence of conflict avoidance among the King Island Inupiat - Kingston, Deanna (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractDuring the summers of 2005 and 2006, a group of Ugiuvangmiut (King Island Inupiat) and western scientists participated in a project entitled “Documenting the Cultural Geography, Biogeography, and Traditional Ecological Knowledge of King Island, Alaska.” The intent was to bring Ugiuvangmiut to King Island in order to document and map place names, as well as archaeological and subsistence sites. Throughout fieldwork, conflicts occurred between scientists, between community members, and between scientists and community members. As the principal investigator, I confronted one conflict in 2005, but my actions exacerbated long-standing tensions within the community and I was later advised by two community members that I should not have confronted the conflict. When conflict occurred again in 2006, instead of confronting the conflict, I chose to take a break from the project for several days. The result was that the overt conflict within the community lessened. Based upon these experiences and other examples, I conclude that conflict avoidance still persists among the Ugiuvangmiut. In addition, I “write against culture” (to borrow Abu-Lughod’s phrase) to explain how my mixed ethnic background and the backgrounds of two community members resulted in actions that run counter to conflict avoidance, showing that there are “multiple, shifting, and competing” cultural values at play. I end with suggestions for scientists conducting fieldwork in the North.